Transformative Leadership of Village Heads in Enhancing Public Participation (A Case Research in Paloh Gadeng Village, North Aceh) - Muhammad Balya; Randy Mahardhika Putra; Ricky Purnomohadi; Kurniati Kurniati (Journal Research of Social Science, Economics, and Management, 2025)
The leadership of the village head plays a vital role in boosting community participation in public decision-making, especially in areas characterized by strong social and cultural dynamics, such as Paloh Gadeng Village in North Aceh Regency. This research aims to assess how effective village head leadership is in encouraging citizen involvement in the planning, implementation, and evaluation of village policies. A qualitative approach using a case research design was adopted. Data collection included in-depth interviews, questionnaires, and participatory observation involving thirty informants, such as the village head, community leaders, and residents. The results show that open communication, transparency in managing information, and the integration of local cultural practices are key factors in promoting active community involvement. The research highlights that village heads who can incorporate local values within a participative leadership framework are more likely to succeed in developing responsive and legitimate policies at the village level.